PS 05-59 Pulse Wave Velocity and Carotid Intima Medial Thickness: Age and Arterial Hypertension Related Alterations. (September 2016) - Ramirez, Agustin; Diaz, Alejandro; Galli, Cintia; Tringler, Matias; Fischer, Edmundo Cabrera
Abstract : Objective: Carotid artery intima-media thickness (CCIMT) and pulse wave velocity (PWV) are considered as surrogates of arterial stiffness and related to cardiovascular risk (CVR). To analyze, in normotensive subjects (NT), without CVR: the age related normal values for CCIMT and PWV, their relationship and the rate of changes with aging. In subjects with arterial hypertension (HT), as unique risk factor (RF), the age and hypertension impact on PWV and CCIMT. Design and Method: 1079 subjects were randomly enrolled and divided in asymptomatic non-smoking NT (n = 780, 40 ± 8.5 years old), without diabetes, dyslipidemia and first degree family history of hypertension and asymptomatic non-smoking HT, as only RF, (n = 299, 50 ± 14.8 years old). In 611 out of the 1079 subjects included (39.8 ± 16.5 years), the reference values of CCIMT and the 95% confidence intervals values were also calculated for each decade of age (10–81 years). Carotid-Femoral PWV was continuously measured for, at least 10 cardiac cycles, and the mean value considered as the subject PWV. CCIMT was measured with a B mode ultrasound echocardiograph (EsaoteMyLab 40) with specific software. Results: In NT, mean PWV value was 6.85 ± 1.66 m/s with a linear increase related with age (r = 0.79; p < 0.05) and a decade growth of 0.245 m/sec. Similarly, CCIMT mean value was 0.554 ± 0.130 mm and increases linearly with aging (r = 0.79; p < 0.05), with a progressive decade related increase (0.06 ± 0.001 mm). In HT, mean PWV value was 8.04 ± 1.8 m/s (p < 0.01) and, as in NT, increased linearly with age (r = 0.49; p < 0.05) with a decade growing of 0.589 m/sec (p < 0.001). PWV and IMT were significantly related (r = 0.42, p < 0.001). No gender differences were observed either in NT or HT. Conclusions: It is suggest that CVR related to the ageing process is further increased when other RF, as arterial hypertension, are added.